Selected to represent Cyprus at the 51st Venice Biennale International Art Exhibition - Sofokleous, Konstantina (My University, 2026)
While still at University, selected to represent Cyprus at the 51st Venice Biennale International Art Exhibition with Animation and Drawings. Organized by Cyprus Ministry of Education and Culture
Keywords: Arts and entertainment